1997
DOI: 10.1063/1.473815
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of the potential energy surfaces and dynamics of CaNC/CaCN

Abstract: Potential energy surfaces for the ground and two low-lying electronically excited states of CaNC/CaCN, are calculated using the ab initio molecular orbital (MO) configuration interaction (CI) method. The absorption and emission spectra of the system are computed by performing time-dependent quantum dynamical calculations on these surfaces. The most stable geometries for the two lowest lying 12Σ+ and 12Π electronic states correspond to the calcium isocyanide (CaNC) structure. These two states are characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…The derived column density of CaNC has to be considered as an upper limit because IR pumping through the low-energy ν 2 bending mode has not been considered in our calculations. Nambu et al (1997) have performed ab initio calculations for the potential energy surface of CaNC and found that the bending frequency could be particularly low (≃27 cm −1 ). Following Agúndez & Cernicharo (2006) and Agúndez et al (2017), infrared pumping can significantly increase the population of intermediate and high- N molecular levels with respect to the pure collisional excitation case.…”
Section: Discussionmentioning
confidence: 99%
“…The derived column density of CaNC has to be considered as an upper limit because IR pumping through the low-energy ν 2 bending mode has not been considered in our calculations. Nambu et al (1997) have performed ab initio calculations for the potential energy surface of CaNC and found that the bending frequency could be particularly low (≃27 cm −1 ). Following Agúndez & Cernicharo (2006) and Agúndez et al (2017), infrared pumping can significantly increase the population of intermediate and high- N molecular levels with respect to the pure collisional excitation case.…”
Section: Discussionmentioning
confidence: 99%
“…Both experimental and supporting theoretical studies have shown that the bonding in these states is strongly ionic and the unpaired electron resides primarily on the metal atom. [7][8][9][10][11][12][13] Pure rotational spectra for MgNC, [14][15][16][17] MgCN, 18 and CaNC 19,20 have also been recorded. One of the catalysts for the recent interest in the metal cyanides/isocyanides was the observation of both MgCN and MgNC free radicals in interstellar space.…”
Section: Introductionmentioning
confidence: 99%
“…16 From the l-type doubling constant, the bending frequency was found to be low, with an estimated value of 86 cm -1 . No corresponding rotationally resolved data are available for the heavier alkalineearth isocyanides; however, ab initio calculations have been performed on CaNC, and these calculations have predicted a bending frequency of 27 cm -1 in the ground electronic state, 13 suggesting a highly floppy system.…”
Section: Introductionmentioning
confidence: 99%
“…The isomerism (or polytopism) of many metal cyanides, including the lithium, 1f,2c-e,, sodium, , magnesium, 2g, potassium, 2b,e,4c,5f, and calcium 6a,i,8 monocyanides, has been investigated both experimentally and by ab initio methods. A general trend evident in these studies has been that alkali metal monocyanides preferentially adopt a π-complex structure 2,3,7 (although this does not hold true for the smallest alkali metal, lithium) while the alkaline earth monocyanides are more prone to form a linear isocyanide MNC. , In some instances, notably the cation Mg(CN) + , 6f-h all three geometries, linear MCN, linear MNC, and π-complex, are seen to be local minima according to high-level ab initio calculations, with comparatively small barriers to interconversion.…”
Section: Introductionmentioning
confidence: 99%